PENINGKATAN PEMAHAMAN POTENSI DIRI MELALUI LAYANAN INFORMASI BIDANG BIMBINGAN PRIBADI PADA SISWA KELAS XI IPA 2 SMA N 1 CEMPAGA TAHUN 2015/2016 - Agus Heriyanto; Jayadi Jayadi; Junaidi Junaidi (Jurnal Paedagogie Media Kependidikan, Keilmuan dan Keagamaan, 2019)
This research aim to to know there is not the make-up of the understanding of potency of x'self of student of class of XI IPA 2 passing service of personal tuition area information in SMA N 1 Cempaga school year 2015 / 2016. Subyek in this research is student of class of XI IPA 2 SMA N 1 Cempaga school year 2015 / 2016 amounting to 35 student. technique of Intake sampel use the saturated technique sampel. Hypothesis raised in this research is there is the make-up of the understanding of potency of x'self of student of class of XI IPA 2 through service of personal tuition area information in SMA N 1 Cempaga [of] School Year 2015 / 2016. Data collecting conducted to use the scale of[is understanding of potency of student x'self, while method used for the examination of hypothesis is test t-test with the technique of paired sample t-test.Hasil analyse obtained [by] value thitung = 10,361 > ttabelpada signifikansi 5% that is 2,0322. This means there is the make-up of the understanding of potency of student x'self of passing service of personal tuition area information.